Blood-Borne ST6GAL1 Regulates Immunoglobulin Production in B Cells - Irons, Eric E.; Punch, Patrick R.; Lau, Joseph T. Y. (Frontiers in Immunology, 2020)
Humoral immunity is an effective but metabolically expensive defense mechanism. It is unclear whether systemic cues exist to communicate the dynamic need for antigen presentation and immunoglobulin production. Here, we report a novel role for the liver-produced, acute phase reactant ST6GAL1 in IgG production. B cell expression of ST6GAL1, a sialyltransferase mediating the attachment of a2,6-linked sialic acids on N-glycans, is classically implicated in the dysregulated B cell development and immunoglobulin levels of St6gal1-deficient mice. However, the blood-borne pool of ST6GAL1, upregulated during systemic inflammation, can also extrinsically modify leukocyte cell surfaces. We show that B cell independent, extracellular ST6GAL1 enhances B cell IgG production and increases blood IgG titers. B cells of mice lacking the hepatocyte specific St6gal1 promoter have reduced sialylation of cell surface CD22 and CD45 and produce less IgG upon stimulation. Sialylation of B cells by extracellular ST6GAL1 boosts expression of IgM, IgD, and CD86, proliferation, and IgG production in vitro. In vivo, elevation of blood ST6GAL1 enhances B cell development and systemic IgG in a CD22- dependent manner. Our data point to a function of an extracellular glycosyltransferase in promoting humoral immunity. Manipulation of systemic ST6GAL1 may represent an effective therapeutic approach for humoral insufficiency